DISIPLIN KERJA GURU SMK NEGERI 1 TANAH PUTIH KABUPATEN ROKAN HILIR - Yanti, Devi; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Based on Government Regulation No. 53 of 2010 Concerning Civil Servant Discipline described in Chapter II Obligations and Prohibition Article 3, paragraph 11, 12 and 17 affirmed that the civil servants, including teachers, are required to come to work and comply with the terms of working hours and the civil service employee shall achieve the goals set forth and obey the rules set by the official authorities. Field observations there are problems in SMK Negeri 1 Tanah Putih among others, the teachers are often not present in the teaching, the teacher was present and did not come home on time for no apparent reason, the class that does not implement the learning process. This study aims to determine labor discipline teacher in SMK Negeri 1 Tanah Putih Rokan Hilir District and the factors that hinder the implementation.The author uses the theory of discipline according to Anwar Prabu Mangkunagara that preventive discipline (attempt to work the discipline) and corrective discipline (implementation of disciplinary sanctions). This study used a qualitative descriptive approach using key informant with data collection using interviews, observation, and documentation.Work Discipline research results Teachers SMK Tanah Putih 1 Rokan Hilir is still not discipline, it is because SMK N 1 Tanah Putih has not been able to exercise the discipline of preventive and corrective discipline optimally.Inhibiting factors in the discipline of teachers, among others: the persistence of negligence on the part of teachers in implementing the obligation of the school, the lack of responsibility of a teacher to his students in the learning process, a lack of supervision and the imposition of sanctions by the school, the salaries are slightly obtained by the highest honor teachers only 1 (one) million. With salaries like that principals can apply less rigor because the discipline does not fit what is acceptable to the responsible work. Still the teachers who do not master science and technology. There is still a lack of facilities and infrastructure SMK Tanah Putih N 1 is of means of information (internet) as well as practice equipment.Keywords : Discipline, Work, Teachers